Two types of higher-order readings of wh-questions - Xiang, Yimei (Proceedings of the Amsterdam Colloquium, 2019)
Evidence from questions with modals and collective predicates suggests that sometimes wh-questions must be interpreted with higher-order readings. In such readings, questions expect answers naming generalized quantifiers rather than entities. This paper investigates the distribution and the derivation of those readings. First, I argue that the generalized quantifiers that can serve as semantic answers to questions are subject to two constraints —Positiveness and Homogeneity. Next, I present two ways to account for a distributional constraint with higher-order readings, that is, questions with a singular-marked or numeral modified wh-complement admit elided disjunctive answers but not conjunctive answers.